KEUTAMAAN ILMU DALAM PERSPEKTIF PENDIDIKAN ISLAM: KAJIAN QS. AL MUJADILAH AYAT 11 - Fatimah Fatimah; Sarwadi Sulisno (Adisam Publisher, 2026)
This study aims to analyze the concept and virtue of knowledge as presented in QS. Al-Mujādilah verse 11 and its implications for Islamic education. The problem addressed in this research is the tendency of modern education to separate intellectual development from spiritual and moral values, leading to an imbalance in holistic human development in shaping a whole human being. This study employs a qualitative approach using library research methods by examining classical and contemporary tafsīr sources, such as Tafsir Ibn Kathir, Tafsir al-Jalalayn, and Tafsir al-Mishbah, along with relevant academic literature. The data were analyzed descriptively and thematically to reveal the educational values embedded in the verse. The results show that QS. Al-Mujādilah verse 11 emphasizes the integration of faith, knowledge, and manners (adab); positions knowledge as a means of attaining higher moral and spiritual status; and highlights the ethical responsibility of scholars to apply their knowledge for the benefit of society. Thus, the verse provides a conceptual foundation for developing an integrative and transformative Islamic education system oriented toward forming the insān kāmil, a complete and virtuous human being